EVALUASI PELAKSANAAN PROGRAM SISTEM KREDIT SEMESTER DI MAN 2 MODEL MEDAN - Syaukani; Ridhali Raja Mandadwika; Ahmad Badren Siregar; Febriani Rambe; Wiwik Safura; Roslina; Rahmat Fajar; Rahmat Nur Utama; Rieke Widyas Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to evaluate the implementation of the Semester Credit System (SCS) Program at MAN 2 Model Medan using the CIPP (Context, Input, Process, Product) evaluation model. The study employed an evaluation research design with a mixed-methods approach combining quantitative and qualitative data. Quantitative data were collected through questionnaires distributed to teachers and students participating in the SCS Program, while qualitative data were obtained through interviews, observations, and document analysis. The research informants consisted of the principal, vice principal for academic affairs, and the SCS program coordinator. The respondents included subject teachers and 15 students enrolled in the SCS Program. Quantitative data were analyzed using descriptive percentage techniques, whereas qualitative data were analyzed using the Miles, Huberman, and Saldaña interactive model, including data reduction, data display, and conclusion drawing. The findings revealed that the context aspect was categorized as good, with students' understanding of the program reaching 80%. The input aspect demonstrated adequate resource readiness with an average percentage of 84.67%. The process aspect was categorized as very good, with learning implementation reaching 86% and academic guidance and counseling support reaching 88%. The product aspect indicated that the SCS Program provided significant benefits to students, achieving a percentage of 89%. Overall, the Semester Credit System Program at MAN 2 Model Medan achieved an average score of 85.00%, categorized as good. Based on the CIPP evaluation results, the program is considered feasible to continue with several improvements related to program socialization, academic mentoring, administrative systems, and teacher competency development.